ORGANIC POTATO PRODUCTION – THE BIODYNAMIC WAY - Upadhayay, N C; Khan, M. A; Shukla, Arvind K.; Singh, O P. (Potato Journal, 2013)
Field experiments were conducted in Typical Ustochrept soil of Modipuram from 2002-03 to 2004-05 to produce organic potato, following principles of biodynamic farming. In the first year, the highest tuber yield (190.7 q ha-1) was obtained in Kufri Anand followed by Kufri Sutlej (173.5 q ha-1). In case of Kufri Chipsona-1, Kufri Bahar, Kufri Pukhraj and Kufri Chipsona-2, the aggregate tuber yields were 155.2, 152.6, 136.0 and 120.4 q ha-1, respectively. The continuous raising of organic potato bio-dynamically on the same site, improved tuber production by 30-50%. A perusal of grade-wise tuber production revealed that biodynamically raised organic potato produced 8-11% more seed size tubers than inorganically fertilized crop.